DESIGN of AUTOMATIC ORGANIC WASTE CRUSHER USING ARDUINO MICROCONTROLLER - Islamiyah, Mufidatul; Kala'lembang, Adriani (Merdeka Malang University, 2018)
Organic waste is the residual daily activities of humans or natural processes in the form of solid or semi-solid in the form of organic or inorganic substances that are biodegradable or unraveled which are considered useless and disposed of in the environment. This organic waste can be used as fertilizer for plants if processed properly, therefore this waste can be used as fertilizer processing by destroying, so this study aims to create a tool that can destroy waste so that it is easy to process using an Arduino microcontroller, the design is done ranging from hardware to software. The way the device works is to detect the material to be destroyed, then the system will be active, the tool is designed a choice of time for the material to be destroyed so that the appliance will automatically die when the time expires and the choice of blade rotation speed from maximum, medium to minimum. From the experiments carried out the tool was able to destroy the material until smooth.DOI :Â https://doi.org/10.26905/jeemecs.v1i2.2377